Prognosis in head and neck cancer: the importance of the patient-, and treatment-related factors - Yücel, Birsen; Fuat Eren, Mehmet; Akkaş Atesever, Ebru; Kaçan, Turgut; Hasbek, Zekiye; Metin Şeker, Mehmet (ENT Updates, 2013)
Objective: To investigate the importance of comorbidity, performance status, hemoglobin level, weight loss, interruption of radiotherapy, and mucositis as prognostic factors in head and neck cancer patients. Methods: Two-hundred and ten patients who were admitted to the Oncology Center of our university between 2006 and 2012, and treated for head and neck cancer were included in the study. Performance status at admission was evaluated according to Eastern Cooperative Oncology Group (ECOG) scoring system. Staging of the disease was based on TNM staging system revised in 2010. Results: The median follow-up period was 24 (range: 1-134) months. Recurrence was observed in 24% of the patients in a median 11 (range: 3-96) months. Metastasis was observed in 13% of patients, in the median 15 (range: 1-134 months). The 3-year local control, overall survival and disease-free survival rates were 72%, 59%, and 53%, respectively for all patients. The factors affecting the 3-year local control rates in univariate analysis were performance status (p=0.006), weight loss (p=0.002), localization (p=0.003), and stage (p<0.001) of the disease, and perineural invasion (p=0.011). The 3-year overall survival rates were not influenced by comorbidity (p=0.045), performance status (p<0.001), hemoglobin level (p<0.001), weight loss (p<0.001), perineural invasion (p=0.017), lymphovasculer invasion (p=0.022), localization (p=0.007), and stage of the disease (p<0.001), and interruption of radiotherapy (p=0.041). The prognostic factors for the 3-year disease-free survival were comorbidity (p=0.045), hemoglobin level (p<0.001), weight loss (p<0.001), perineural invasion (p=0.017), lymphovascular invasion (p=0.022), localization (p=0.007), and stage of the disease (p<0.001). Conclusion: Weight loss and perineural invasion for local control; performance status, weight loss, hemoglobin level, and interruption of radiotherapy for overall survival; performance status, weight loss, and hemoglobin level for disease-free survival were found to be independent prognostic factors in multivariate analysis.